Assessment of the factorial structure of the Survey of Interpersonal Values - Merino Soto, César (2004)
The present study evaluates the factorial structure, in the leve! of the subscales, of the Survey of Interpersonal Values (SIV), and the relationships among them, in a sample of adolescents between 15 and 17 years old of both sexes and from a private and public school, representative of low and middle socioeconomic Ievels. Although the SIV has been a widely used too!, there is no report of ah analysis of its factorial structure in Latín-American samples. By means of the principal components analysis and the factorial analysis with a confirmatory approach, bipolar relationships have been identified between Independence and Benevolence, and Support and Conformity. The confirmation of the pattem of interpersonal values proposed by L. V. Gordon was also accomplished. An aspect considered in the analysis may have artificially influenced the pattern of correlations among the components, and the reliability: the ipsative method of the questions of the SIV. Finally, there is a discussion about the ipsative measurement and its consequences in the interpretation of the results.